Effect of Storage Time of Epididymis at 5 oC on Spermatozoa Quality of Aceh Local Goat - Hamdan, Hamdan; Panjaitan, Budianto; Sutriana, Amalia; Aliza, Dwinna; Rahmi, Erdiansyah (Universitas Syiah Kuala, 2010)
The objective of this study was to evaluate the effect of storage time of epididymis at 5 oC on spermatozoa quality of Aceh local goat. This research was conducted at Reproduction Laboratory, FKH Unsyiah from May to June 2009. Nine epididymis from local goat at the age of 1.5-2.0 years were used in this study. The epididymis were collected from abattoir in Banda Aceh. The experimental design used in this study was completely randomized design with 3 treatments and 3 replications. Spermatozoa quality which consist of sperm concentration, motility, amount of life sperm, and sperm abnormality were examined after the collection of epididymis on day 0 (H-0), day 1 (H-1), and day 3 (H-3) post storage at 5 oC. Data were analyzed using one-way analyses of variance (ANOVA). The result showed that no significant difference (P0.05) seen in the spermatozoa quality after different storage time. The average of spermatozoa concentration on H-0, H-1, and H-3 were 318x107/ml, 282x107/ml, and 241x107/ml respectively. On the average, the percentage of spermatozoa motility on H-0, H-1, and H-3 were 82,272,75; 80,252,83; and 78,070,92%, respectively. Life spermatozoa observed on H-0, H-1, and H-3 were 82,292,71; 80,631,87; and 80,093,31%, respectively. Observation on spermatozoa abnormality showed that the average of spermatozoa abnormality on H-0, H-1, and H-3 were 7,230,27; 8,210,55; and 10,753,14%, respectively. It could be concluded that the spermatozoa quality were not affected by the storage time at temperature of 5 oC.